Toe-walking in heterozygous carriers of McArdle disease - D. Pomarino; A. A. Emelina; J. R. Thren; K. Rostazy (Лечащий Врач)
McArdle disease (glycogen storage disease type V) is a metabolic myopathy often onset in the first decade of life. The main symptoms of the disease include myalgia and fatigue in the first few minutes of exercise, as well as its intolerance, including contractures, stiffness and / or weakness of the muscles used. These symptoms are usually precipitated by isometric exercise (eg, weight lifting) or long-term vigorous aerobic exercise (eg, stair climbing, jogging), and often improve with rest. The literature describes the clinical heterogeneity of the symptoms of the disease – in addition to a severe, rapidly progressive form, 10% of patients have mild manifestations (for example, fatigue and low endurance, but without the formation of contractures) or a practically asymptomatic course in everyday life. Weakness, which occurs in about 20% of patients, is more likely to involve the proximal muscles and is more common in people over 40 years of age. It is noteworthy that the PYGM gene variants are characterized by phenotypic heterogeneity; two patients may have an identical genetic variant but show symptoms of varying severity. This article describes a clinical case of a 9-year-old patient with the c.1354G>A, Ala452Thr mutation in the PYGM gene. Mutation of this gene is associated with McArdle disease, which has a recessive mode of inheritance. The examined heterozygous carrier of the gene had mild symptoms of the disease, among which the main ones were fatigue and toe walking. Due to the formed deformity of the feet, it was decided that surgery was necessary. The patient underwent percutaneous myofasciotomy. The postoperative period passed without complications. When examined after 6 months, there was no recurrence of walking on toes. Thus, the manifestations of McArdle disease are very diverse, they can manifest, among other things, in the form of gait anomalies and foot deformities, including in carriers of the gene.